The Effect of Work Environment and Motivation on Teacher Work Discipline (Case Study on Teachers at SMKS Galuh Rahayu, Ciamis Regency) - Nancy Savitrie Setiadi; Rita Tri Yusnita; Arga Sutrisna (Journal of Indonesian Management, 2022)
This research was conducted with the aim of knowing the effect of the work environment and motivation on work discipline at SMKS Galuh Rahayu teachers. The method used in this research is a case study using data obtained directly through questionnaires distributed to 26 respondents who are teachers of SMKS Galuh Rahayu. The technique used in this research is path analysis. The results of the study indicate that: (1) the work environment has a positive and significant effect on motivation for teachers at SMKS Galuh Rahayu; (2) The work environment directly has a positive and but not significant effect on Work Discipline at Galuh Rahayu Vocational School Teachers; (3) Motivation directly has a positive and significant effect on Work Discipline at SMKS Galuh Rahayu Teachers; (4) The work environment has a positive and significant effect on work discipline through motivation for teachers at SMKS Galuh Rahayu.